The Anterolateral Ligament of the Knee: An Inconsistent Finding in Pediatric Cadaveric Specimens. Issue 5 (July 2016) - Shea, Kevin G.; Polousky, John D.; Jacobs, John C.; Yen, Yi-Meng; Ganley, Theodore J.
Abstract : Background: The anterolateral ligament (ALL) of the knee has been identified as a structure that limits internal rotation, and thus, affects the pivot shift mechanism. It has previously been reported in a high percentage of adult subjects. The purpose of the current study was to evaluate whether the ALL could be identified on pediatric cadaveric knee specimens and compare these findings to previously published reports. Methods: Eight skeletally immature cadaver knee specimens were examined through gross dissection: ages 3 months, 4 months, 1 year, 2 years, 3 years, 3 years, 8 years, and 10 years. There were 3 male and 5 female (7 right, 1 left) specimens. The presence or absence of the ALL was documented in each specimen, through dissection, intermittent internal and external rotation of the tibia, and anterior translation of the tibia, to produce tension of the lateral collateral tissues and joint capsule. These dissections were performed by a group of fellowship-trained orthopaedic surgeons. Results: The iliotibial band, entire lateral joint capsule, lateral collateral ligament, and popliteus were readily identified in each specimen. In 7 specimens, a distinct ALL structure was not identified during dissection. The ALL was identified in 1 of 8 specimens (1-year-old female, right knee). The ALL was further delineated under applied internal rotational stress. Conclusions: Previous research has suggested that this ligament is present in the majority of adult specimens. This finding was not reproduced in the current study of pediatric cadaveric specimens, where only one of 8 specimens had an identifiable ALL. This suggests that this ligament may develop later in life, after physiological loads are applied to the joint capsule. Further research in both adult and pediatric knees needs to be conducted to further elucidate the development of this ligament, and the role of this structure in knee stability. Clinical Relevance: The ALL is a knee ligament that has been described in adults. However, it is unclear whether this structure is present or fully developed in younger populations. The current study sought to identify the ALL in pediatric cadaver knee specimens, identifying this structure in only one of 8 specimens. The findings of this study suggest that the ALL may be an inconsistent structure in the pediatric population.